Beyond brushtalk : Sino-Japanese literary exchange in the interwar period - Keaveney, Christopher T. (UPCC book collections on Project MUSE., 2009)
Christopher Keaveney explores interactions between Japanese and Chinese writers from 1919 to 1937. During this period, there were unprecedented opportunities for exchange between writers which was made possible by the ease of travel between Japan and China and the educational background of Chinese writers as students in Japan.